Encyclopedia of Polymer Science and Technology 2010
DOI: 10.1002/0471440264.pst014.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Adsorption

Abstract: Adsorbed polymers at interfaces are used to control interactions between surfaces in a wide range of applications such as lubrication, adhesion, food processing, and paints. Recent developments have enabled new applications using adsorbed polymers to create surfaces capable of regulating cell adhesion and proliferation. This article summarizes the current theoretical understanding of polymer adsorption and the experimental techniques used to study adsorption of neutral and charged polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…As a result, many bacterial strains and species have become resistant to gentamicin . To overcome such issues, several types of layer-by-layer (LbL) polymer coatings that incorporate antibacterial compounds and continuously release them in a highly localized manner have been explored. One of the ways has been using pH-responsive drug delivery systems such as pH-responsive coatings. A significant recent development includes a new family of LbL coatings, which do not elute antibiotics under normal, infection-free conditions, but supply antibiotics locally only when activated by bacteria-induced pH lowering …”
Section: Introductionmentioning
confidence: 99%
“…As a result, many bacterial strains and species have become resistant to gentamicin . To overcome such issues, several types of layer-by-layer (LbL) polymer coatings that incorporate antibacterial compounds and continuously release them in a highly localized manner have been explored. One of the ways has been using pH-responsive drug delivery systems such as pH-responsive coatings. A significant recent development includes a new family of LbL coatings, which do not elute antibiotics under normal, infection-free conditions, but supply antibiotics locally only when activated by bacteria-induced pH lowering …”
Section: Introductionmentioning
confidence: 99%
“…A glycoside hydrolase called dispersin B (DspB), which cleaves poly-N-acetylglucosamine polysaccharides, is another example of an enzyme known to disturb biofilm formation by specifically attacking an extracellular polymeric substances component necessary for biofilm formation [68]. Pavlukhina et al showed that a DspB loaded coating was able to reduce Staphylococcus epidermidis surface coverage by 98% [69]. PMAA surface hydrogels on silicon wafers were prepared by depositing bilayers of PMAA/poly(allylamine hydrochloride) (PAH) which were cross-linked using glutaraldehyde.…”
Section: Antibacterial Enzymesmentioning
confidence: 99%
“…Polymers pose a structure-behavior entropic dependency as well as a multiplicity of contacts with surfaces, which causes an amplification of molecular binding. A consequence of such strong binding is that once adsorbed, a polymer chain cannot easily desorb from the surface due to the prohibitively high energetic barrier for desorption, which requires simultaneous detachment of all monomeric units . This atomistic modeling study seeks to provide insights into these phenomena when water is introduced into the system.…”
Section: Introductionmentioning
confidence: 99%
“…Last, because of the commonly nonreactive binding nature (adhesive binding) of many polymer species used, polymers may be less restricted by the availability of soil minerals as raw reactants dictated by the geochemistry of the environment. While the aforementioned resistance to erodibility of the polymer phases would not compromise the polymer-soil composite due to the strong adsorption that is often achieved with the mineral substrate, 18 the durability of the composite "as a whole" could be transiently compromised by the infiltration of water wetting the interparticle interstices and composite interfaces. This is the major potential disadvantage of polymer-soil composites.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation